Effects of Preemergence Herbicides on Bell Pepper, Crop Injury, and Weed Management in Irrigated Chilean Fields. (June 2016) - Figueroa, Rodrigo; Pacheco, Fernanda; Echaiz, Connie; Cordovez, Gabriela; Kuhn, Nathalie
Abstract : Bell pepper is an economically important vegetable crop that is often impaired by weeds. Management of weeds in bell pepper is required to minimize yield loss because this crop does not tolerate weed competition. Several herbicides have been reported as selective for bell pepper, but research supporting their use for weed control in this crop is limited. Several herbicides were screened in a greenhouse to assess effects on plant biomass, and eight were selected that appeared to be safe for bell pepper. These herbicides, in addition to oxadiargyl, were then evaluated at two different Chilean locations, using different application timings. We measured the effects on plant injury, fruit yield, and the need for additional hand weeding on transplanted bell peppers. The herbicides clomazone, napropamide, pendimethalin, and S -metolachlor caused minimal foliar chlorosis and necrosis but did not affect fruit yield at either location. Pretransplant-incorporated application (PTI) caused no effect on fruit yield from the herbicides evaluated, whereas applications 2 wk (POST2) and 8 wk (POST8) after transplanting reduced fruit yield significantly. For weed management, the best combination was PTI + POST2 + POST8, which reduced the hand-weeding time by 30% compared to the control, at both locations. Based on our results, clomazone, pendimethalin, and S -metolachlor were the most effective treatments applied after transplanting, whereas all herbicides tested were selective for bell pepper when applied and incorporated before transplanting. Results presented here provide new insight into herbicides that can be used to manage weeds in bell pepper and shows that timing of herbicide application is critical to prevent injury to this crop.